Receptor Tyrosine Phosphatases Guide Vertebrate Motor Axons during Development - Stepanek, Laurie (J Neurosci, 2005)
Receptor-type protein tyrosine phosphatases (RPTPs) are required for appropriate growth of axons during nervous system development in Drosophila. In the vertebrate, type IIa RPTPs [protein tyrosine phosphatase (PTP)-δ, PTP-σ, and LAR (leukocyte common-antigen-related)] and the type III RPTP, PTP receptor type O (PTPRO), have been implicated in the regulation of axon growth, but their roles in developmental axon guidance are unclear. PTPRO, PTP-δ, and PTP-σ are each expressed in chick motor neurons during the period of axonogenesis. To examine potential roles of RPTPs in axon growth and guidance in vivo, we used double-stranded RNA (dsRNA) interference combined with in ovo electroporation to knock down RPTP expression levels in the embryonic chick lumbar spinal cord. Although most branches of the developing limb nerves appeared grossly normal, a dorsal nerve identified as the anterior iliotibialis was clearly affected by dsRNA knock-down of RPTPs. In experimental embryos treated with dsRNA targeting PTP-δ, PTP-σ, or PTPRO, this nerve showed abnormal fasciculation, was reduced in size, or was missing entirely; interference with PTPRO produced the most severe phenotypes. Control embryos electroporated with vehicle, or with dsRNA targeting choline acetyltransferase or axonin-1, did not exhibit this phenotype. Surprisingly, embryos electroporated with dsRNA targeting PTP-δ together with PTPRO, or all three RPTPs combined, had less severe phenotypes than embryos treated with PTPRO alone. This result suggests that competition between type IIa and type III RPTPs can regulate motor axon outgrowth, consistent with findings in Drosophila. Our results indicate that RPTPs, and especially PTPRO, are required for axon growth and guidance in the developing vertebrate limb.